2021
DOI: 10.3390/biomedicines9020160
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1α Gene-Activated Collagen Scaffold Restores Pro-Angiogenic Wound Healing Features in Human Diabetic Adipose-Derived Stem Cells

Abstract: Non-healing diabetic foot ulcers (DFUs) can lead to leg amputation in diabetic patients. Autologous stem cell therapy holds some potential to solve this problem; however, diabetic stem cells are relatively dysfunctional and restrictive in their wound healing abilities. This study sought to explore if a novel collagen–chondroitin sulfate (coll–CS) scaffold, functionalized with polyplex nanoparticles carrying the gene encoding for stromal-derived factor-1 alpha (SDF-1α gene-activated scaffold), can enhance the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 107 publications
1
31
0
Order By: Relevance
“…Murine diabetic models have found that the use of adipose- [ 200 ], umbilical- [ 201 ], bone-marrow- [ 202 ], and smooth-muscle [ 203 ]-derived stem cells or combination therapies with MSCs [ 204 , 205 ] accelerated wound healing. As diabetic-derived stem cells have an impaired healing phenotype, modification of MSCs by selective gene overexpression such as stromal-cell-derived factor (SDF)-1α [ 180 ], overexpression of c-Jun [ 181 ], depletion of miR-205-5p [ 103 ], or by photobiomodulation [ 238 ] have shown promising results in promoting wound healing and provides potential pathways for autologous stem cell treatment. In humans, the injection of autologous micro-fragmented adipose tissue [ 239 ] and combination therapies with umbilical cord MSCs improved healing outcomes [ 240 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Murine diabetic models have found that the use of adipose- [ 200 ], umbilical- [ 201 ], bone-marrow- [ 202 ], and smooth-muscle [ 203 ]-derived stem cells or combination therapies with MSCs [ 204 , 205 ] accelerated wound healing. As diabetic-derived stem cells have an impaired healing phenotype, modification of MSCs by selective gene overexpression such as stromal-cell-derived factor (SDF)-1α [ 180 ], overexpression of c-Jun [ 181 ], depletion of miR-205-5p [ 103 ], or by photobiomodulation [ 238 ] have shown promising results in promoting wound healing and provides potential pathways for autologous stem cell treatment. In humans, the injection of autologous micro-fragmented adipose tissue [ 239 ] and combination therapies with umbilical cord MSCs improved healing outcomes [ 240 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…In previous studies, ASCs are inferred to influence the procedure of inflammation in chronic wounds by paracrine effects to suppress inflammation ( 30 ). To further verify the opinion, several studies evaluated the inflammatory cytokine variation in rat ASCs treated diabetic wounds ( 45 , 48 , 52 ). Cytokines such as IL-6, IL-8 are significantly deregulated in diabetic and non-diabetic ASCs treated wounds.…”
Section: Mechanisms Of Ascs To Promote Diabetic Wound Healingmentioning
confidence: 99%
“…In a study conducted by Laiva et. al, the application of SDF-1α scaffold, which promotes ASCs proliferation, showed no significant effect on high inflammatory cytokine caused by diabetic ASCs, indicating ASCs do not function as inflammatory cytokine secretion ( 52 ). In pre-clinical studies, human ASCs are used in diabetic wounds.…”
Section: Mechanisms Of Ascs To Promote Diabetic Wound Healingmentioning
confidence: 99%
“…Hence, the SDF-1α gene-activated scaffold can overcome the deficiencies associated with diabetic ADSCs, paving the way for autologous stem cell therapies combined with novel biomaterials to treat DFUs. Moreover, the transfected diabetic ADSCs also exhibited pro-wound healing features like active matrix remodelling of the provisional fibronectin matrix and basement membrane protein collagen IV [ 116 ], which is not only essential for supporting the adhesion and migration of cells, but also provides a scaffold for subsequent collagen deposition [ 126 ]. A similar in vivo study used human-induced pluripotent stem cell-derived smooth muscle cells (hiPSC-SMC) instead of ASC, combined with collagen scaffold to treat diabetic mouse [ 115 ].…”
Section: Combinational Therapy Using Both Biomaterials and Stem Cell In Wound Healing And Regeneration Treatmentmentioning
confidence: 99%